Secrets to Success in Informal Sector Financial Compliance: Utilizing New Technological Application for Improved Community Health Program Efficiency and Effectiveness - Minyenya, Joy; Adam, Mary; Mathuku, James; Kamiru, Wilson; Mbugua, Simon; Gichimu, Jacob (Machakos University, 2018)
Secrets to success in informal sector financial compliance: Utilizing new technological applications for improved community health program efficiency and effectiveness Financial compliance is an essential aspect of good project management. Most organizations function inside the formal economy for funds disbursement . However, frequently community health activities involve the lowest economic sector consequently working outside the formal economy. Substantial effort to maintain donor related financial compliance exposes staff to individual security risks, loss of resources, cumbersome financial reconciliation, risk of fraud and corrupt procurement procedures. New products in mobile money platforms, recently developed to address needs of businesses operating in the informal sector are available. AIC KIJABE Maternal Newborn Community Health Program adapted a mobile money platform of funds. We customized its protocols to develop best practice for improved compliance in informal sector of community health work to meet needs for transport reimbursements and informal sector catering services. It includes a real-time payment and receipting, combined with an online budgeting for staff which radically improved field work efficiency, reduced financial risks, eliminated carrying hard cash for payments and reduced accounting work effort. Adoption of the new system began in June 2017. The pilot demonstrated reduction in staff hours required for cash procurement, distribution, and accounting from 4 hours to 1 hour for a similar field activity. Additionally, a reduction of multiple trips to one trip by the project vehicle to follow institutional procedures eliminated staff time and saved Ksh6200 on mileage costs. Total estimate savings in terms of hours of productivity for staff deployed reduced effectively, from 4 staff per activity to 2 staff. Improved compliance was noted by our grant management service and adopted across range of their programs in their national scope and they are assessing for a multi-country application of the same in their other programs.
Keywords: Health